Impact of Subchorionic Hematoma on Pregnancy Outcomes in Obstetric Antiphospholipid Syndrome - Cang R; Ding X; Tian Z; Fu Z; He M; Liang Y (International Journal of Women's Health)
Rong Cang,1,* Xuelei Ding,1,* Zan Tian,2 Zijie Fu,3 Meijuan He,1 Ying Liang4 1Department of Gynecological Endocrinology, The Fourth Hospital of Shijiazhuang (Obstetrics and Gynecology Hospital Affiliated to Hebei Medical University), Shijiazhuang, Hebei, People’s Republic of China; 2Department of Dermatology, Hebei Provincial Hospital of Traditional Chinese Medicine, Shijiazhuang, Hebei, People’s Republic of China; 3Department of Gynecology, The First Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 4Department of Reproductive Medicine, The Fourth Hospital of Shijiazhuang (Obstetrics and Gynecology Hospital Affiliated to Hebei Medical University), Shijiazhuang, Hebei, 050011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Liang, Email liangyly@126.comObjective: This study aimed to investigate the effects of subchorionic hematoma (SCH) in patients with obstetric antiphospholipid syndrome (OAPS) on pregnancy outcomes, as well as the clinical value of anticoagulant therapy.Methods: This retrospective study included 109 OAPS patients treated at the Fourth Hospital of Shijiazhuang from December 2019 to December 2021. Patients were divided into two groups: SCH group (n=40) and non-SCH group (n=69). Baseline data, laboratory indicators (anti-β 2GP I, lupus anticoagulant, ACL, D-D, AA, ADP, ATIII, PS, and PC), complications, and pregnancy outcomes were compared between the groups.Results: There were no significant differences between the two groups concerning the abortion rate, live birth rate (all P> 0.05). However, we reported a significantly higher rate of preterm delivery occurring between 34– 37 in the SCH group (13.7% vs 1.7%, P=0.027). The proportion of patients with triple-positive antiphospholipid antibodies (aPLs) was significantly higher in the SCH group compared to the non-SCH group (7.5% vs 0.0%, P=0.047). During pregnancy but before routine first-trimester therapy was initiated, the levels of β 2GP I, LA, ACL, D-D, AA, and ADP in the SCH group were higher than those in the non-SCH group, while ATIII, PS, and PC levels were lower (all P < 0.05). After treatment, the levels of β 2GP I, LA, ACL, D-D, AA, and ADP decreased in both groups compared to their pre-treatment levels (all P < 0.05); however, the levels of D-D and PS in the SCH group remained higher than those in the non-SCH group (all P < 0.05).Conclusion: In patients with OAPS who present with SCH during pregnancy, laboratory indicators suggest more severe immune disorders and coagulopathy, as well as an increased risk of preterm delivery.Keywords: obstetric antiphospholipid syndrome, subchorionic hematoma, anticoagulant therapy, preterm delivery